A Belgian Serosurveillance/Seroprevalence Study of Diphtheria, Tetanus and Pertussis Using a Luminex xMAP Technology-Based Pentaplex - Raissa Nadège Caboré; Denis Piérard; Kris Huygen (Vaccines, 2016)
Serosurveillance and seroprevalence studies are an essential tool to monitor vaccine-preventable diseases. We have developed a magnetic bead-based pentaplex immunoassay (MIA) for the simultaneous detection of IgG antibodies against diphtheria toxin (DT), tetanus toxin (TT), pertussis toxin (PT), filamentous hemagglutinin (FHA) and pertactin (Prn). The in-house pentaplex MIA showed a good correlation with commercial ELISAs with correlation coefficients between 0.89 for PT and 0.98 for TT. Intra- and inter-assay variability was <10%. A total of 670 anonymized serum samples collected in 2012 in Belgian adults (ages 20–29.9 years) were analyzed. Geometric mean concentrations (GMC) were 0.2 (0.13–0.29) IU/mL for DT, 0.63 (0.45–0.82) IU/mL for TT, 3.9 (2.6–5.8) IU/mL for PT, 16.3 (11.7–22.7) IU/mL for FHA and 15.4 (10.1–23.6) IU/mL for Prn. Antibody concentrations were below the protective level of 0.1 IU/mL in 26.4% of the sera for DT and in 8.6% of the sera for TT. Anti-PT IgG concentrations indicative of recent pertussis infection (>125 IU/mL) were detected in 1.2% of the subjects. High anti-PT antibodies were not correlated with high antibodies against any of the four other vaccine antigens. This pentaplex MIA will be used for a new large-scale Belgian serosurveillance/seroprevalence study of diphtheria, tetanus and pertussis.